2001
DOI: 10.1021/ic0104048
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Magnets:  Preparation and Properties of Mixed-Carboxylate Complexes [Mn12O12(O2CR)8(O2CR‘)8(H2O)4]

Abstract: Arrhenius plots obtained from M ′′ versus T data gave effective barriers to relaxation (U eff ) of 71 and 72 K for 5 and 6, respectively. 1 H NMR spectra in CD 2 Cl 2 show that 5 and 6 are the main species present on dissolution, but there is evidence for some ligand distribution between axial and equatorial sites, by intra-and/or intermolecular exchange processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 29 publications
(53 reference statements)
2
67
1
2
Order By: Relevance
“…The crossover can occur in a narrow temperature interval with the field at which the system crosses the anisotropy barrier shifting abruptly with temperature, or the crossover can occur in a broad interval of temperature with this field changing smoothly [15,22,23]. The first studies were published on Mn 12 -Ac [11,12,13] 4 ] was prepared by the carboxylate substitution procedure described elsewhere [25], and crystallizes in triclinic space group P1 [26].…”
mentioning
confidence: 99%
“…The crossover can occur in a narrow temperature interval with the field at which the system crosses the anisotropy barrier shifting abruptly with temperature, or the crossover can occur in a broad interval of temperature with this field changing smoothly [15,22,23]. The first studies were published on Mn 12 -Ac [11,12,13] 4 ] was prepared by the carboxylate substitution procedure described elsewhere [25], and crystallizes in triclinic space group P1 [26].…”
mentioning
confidence: 99%
“…12 Mn 12 molecules have been synthesized with various ligands, and prior studies have showed that magnetic properties and exchange interactions of a SMM are strongly R-dependent. [13][14][15][16][17][18][19] To understand the effect of physical environment on properties of SMMs, especially that of a supporting substrate, it is desirable to place Mn 12 on well-defined surfaces and investigate the electronic and magnetic properties of individual molecules and monolayers. Much effort has already been made to deposit Mn 12 on various substrates, such as the metal Au(111), 20,21 the semi-metal Bi(111), 22 and even the ferromagnetic substrate Ni(111).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spacing between the QMT steps associated with the FR species (~0.4 T) is not all that dissimilar to those of the SR species (~0.45 T), suggesting that they possess similar uniaxial anisotropy constants D. [14][15][16] Subsequently, detailed synthetic work by Christou, Hendrickson and co-workers, involving ligand substitution and crystallization from a variety of solvents, resulted in the discovery of many different forms of Mn 12 possessing essentially the same neutral Mn 12 O 12 core. 11,12,[17][18][19][20][21][22][23][24][25][26][27] However, important differences have been inferred from X-ray and magnetic studies. Most notably, the various Mn 12 complexes can be grouped broadly into two categories, i.e.…”
Section: Introductionmentioning
confidence: 99%